STUDI EKSEGETIS UNGKAPAN MENGUCAP SYUKUR DALAM SEGALA HAL MENURUT 1 TESALONIKA 5:18 - David Susilo Pranoto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2017)
Give thanks is an attitude of the human heart. Giving thanks shows an attitude that is based on a believer's faith in God. Even though this is a simple command, reality shows many believers' failure to give thanks. The Apostle Paul also saw this reality, therefore through 1 Thessalonians, the apostle Paul wanted to give teachings and appeals so that the believers in Thessalonica could show an attitude of life to give thanks. But there are different things that Paul taught with the concept of thanksgiving of unbelievers. Therefore, to understand these differences, it is very important to study thanksgiving from a biblical perspective, in this article specifically doing the exegetical study of the expression